Educação compensatória na EJA: a concepção docente sobre o projeto Filhos da EJA em escolas municipais de João Pessoa-PB - Silva, Kallyne Lygia Ferreira da (2020)
The present study refers to Compensatory Education and to the Filhos da EJA Project in public and municipal schools in João Pessoa - PB, and aims to understand the perception that teachers of the EJA (Youth and Adult Education) modality have regarding the project Filhos da EJA in public schools of João Pessoa-PB. This study was conducted in the period of 2018-2019, from the perspective of qualitative approach and based theoretically in the Historical and Dialectical Materialism. Dialectical Materialism, as a method, enables the investigation of a phenomenon in its interaction with the world and the context it is inserted in, identifying cause and effect, as well as the existing contradictions. The empirical research was performed in three public municipal schools in João Pessoa-PB, with eight (08) teachers that work in adult education. Thus, we used the semi structured interview, as an information gathering instrument, in order to elucidate the questions relevant to the research. The study on compensatory education and the Filhos da EJA project in public and municipal schools in João Pessoa-PB exposed not only the historical trajectory of denial of access to education, but also the reproduction of palliative projects for the EJA modality, the contradiction between theory and practice in basic education, and the relationship between quantity and quality in the offer of this teaching modality. Historically, we have pointed out advances and setbacks that reproduce an education that is aid-based, compensatory and does not addresses the full-picture. The research dealt with the empirical categories of access, permanence, and evasion. Regarding the access, we observed that it is essential in the educational field, but is not enough to keep the student in the school by itself, since permanence is a diffuse process that is related to factors both internal and external to the school, such as the socioeconomic condition of the student, which ends up leading to school dropout. Therefore, these categories allowed the assimilation of the empiric phenomenon and the research’s development. In the final remarks, we verified that the teachers point that the Filhos da EJA Project provides security and acceptance. However, they consider that this is not a determinant factor for the student’s permanence in school. On the other hand, aid-based and compensatory projects in EJA, like the Filhos da EJA Project, undergo a process of naturalization by teachers, being incorporated into school projects. However, we found that the development of the Project in the municipal education system increases the offer of access and accentuates the permanence process as a conditioning factor in the EJA modality